Plyometric jump training micro- and high-dose effects on amateur basketball players athletic performance: a randomized controlled trial - Wu, Bitai; Zhang, Baiming; Yin, Mingyue; Xu, Kai; Ramirez-Campillo, Rodrigo; Huang, Sen; Zhou, Limingfei; Yue, Leijiao; Li, Jianxiong; Liu, Zhifeng; Song, Zhiquan; Zhang, Boyi; et al. (Frontiers in Physiology, 2025)
PurposeTo compare the effects of a 4-week plyometric training program involving microdosing (MPT; four sessions per week, 400 total jumps) and highdosing (HPT; 2 sessions per week, 800 total jumps) on athletic performance in male amateur basketball players.MethodsParticipants were randomly assigned to the MPT (n = 24), HPT (n = 23), or control (CTR; n = 22). The intervention training protocol involved 4 weeks, while the control group received no additional training. Twelve performance metrics were assessed pre- and post-intervention, including countermovement jump (CMJ), countermovement jump with arms (CMJA), 40 cm-drop jump (DJ), reactive strength index (RSI) and modified reactive strength index (RSImod), maximal isometric squat strength, isometric mid-thigh pull (IMTP) rate of force development (RFD), 10 m and 20 m sprint, T-test agility, 5-0-5 test agility, and endurance capacity (yo-yo intermittent recovery test-level 2 - YYIR2). Paired and independent sample t-tests were used to assess within- and between-group (with Bonferroni correction) differences. Effect sizes were calculated using Hedges’ g (g) to quantify the magnitude of training effects.ResultsCompared to the control group, MPT improved CMJ (g = 0.66), RSI (g = 0.96), RSImod (g = 0.71), IMTP (g = 0.64), and 20 m sprint (g = 0.58), and HPT improved RSI (g = 1.08), RSImod (g = 0.88), IMTP (g = 0.64), 20 m sprint (g = 0.79). No differences were observed between MPT and HPT.ConclusionBoth MPT and HPT similarly enhance basketball players’ athletic performance. However, microdosing required reduced training volume to attain a similar magnitude of improvement, representing a time-efficient training alternative.